Quality of life in young onset dementia: an updated systematic review - Baptista,Maria Alice Tourinho (2016)
Introduction Young onset dementia (YOD) develops before 65 years of age and has specific age-related adverse consequences for quality of life (QoL). We systematically examined factors related to the QoL of people with YOD and their caregivers. Method This systematic review used the PRISMA methodology. The literature search was undertaken on July 5, 2015, using Cochrane, PubMed, SciELO, PsycINFO, Scopus and Thomson Reuters Web of Science electronic databases. The search keywords included early onset and young onset combined with, dementia, Alzheimer, vascular dementia, mixed dementia, frontotemporal dementia, quality of life, well-being and unmet needs. Nine studies were included. We revised objectives, study design, sample, instruments and results related to QoL. Results People with YOD rated their own QoL significantly higher than their caregivers. Greater awareness of disease among people with YOD is associated with better QoL in caregivers. A relationship was found between unmet needs and daytime activities, lack of companionship and difficulties with memory. Issues associated with unmet needs were prolonged time to diagnosis, available health services and lack of caregiver's own future perspective. Conclusion Consideration should be given to conducting investigations with more homogeneous samples and use of a clear concept of QoL. The present study highlights the need for future research in a wider range of countries, using instruments specifically for YOD. It would be interesting if studies could trace parallels with late onset dementia groups.